The Effect of the Sport Education Model on Sports Ability: A Critical Systematic Review - Junlong Zhang; Kim Geok Soh; Mohd Ashraff Bin Mohd Anuar; Xiaofei Lin; Nasnoor Juzaily Mohd Nasiruddin (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The comparative efficacy of the Sport Education Model (SEM) and Traditional Teaching (TT) approaches on students' athletic proficiency within Physical Education (PE) instruction, encompassing game performance, technical prowess, and physical fitness, constitutes a significant area of investigation. Yet, a comprehensive assessment discerning the differential impacts of these pedagogical methods on students' athletic capabilities remains wanting. This study endeavours to discern disparities between the Sport Education Model and conventional teaching methodologies in augmenting students' athletic proficiencies. A thorough exploration of scholarly literature was conducted utilizing databases such as Web of Science, PubMed, Scopus, and EBSCOhost (CENTRAL and SPORTDicus). Criteria for study inclusion were formulated utilizing the PICOS framework, stipulating: (i) Population - comprising healthy students; (ii) Intervention - encompassing any SEM intervention program aimed at enhancing students' athletic abilities; (iii) Contrast - spanning any manifestation of traditional teaching methods; (iv) Outcomes - gauged through athletic proficiency metrics, encompassing game performance, technical aptitude, and physical fitness; and (v) Study design - inclusive of randomized controlled trials and non-randomized controlled trials. A total of 12 studies were scrutinized, with five of them being published within the last five years. Methodological rigor was evaluated leveraging the Downs and Black checklist, culminating in an assessment of moderate quality across all studies. The potential for bias within the literature was scrutinized utilizing the ROBINS-I tool, revealing three articles to possess a moderate risk of bias, while the remainder were deemed to exhibit a high risk. Findings derived from predominantly quasi-experimental designs involving college and junior high school students as participants suggest both the Sport Education Model and Traditional Teaching methods to be efficacious in augmenting students' athletic proficiencies, albeit with SEM demonstrating a superior efficacy compared to TT in most instances. Notably, a considerable proportion of studies failed to meet the minimum unit requirement as per Siedentop's guidelines, and model fidelity across many studies remained uncertain. Current evidence underscores the heightened effectiveness of SEM over TT in enhancing students' athletic proficiencies. Nevertheless, the generalizability of findings to wider student demographics remains limited, necessitating further investigation into the efficacy of SEM particularly among primary and high school students. To ensure the reliability and validity of ensuing research endeavours, meticulous attention to intervention planning and design, including considerations of intervention frequency and dosage, is imperative. Moreover, the adherence to model fidelity must be upheld as an indispensable procedural imperative.